Journal of Event, Tourism and Hospitality Studies (JETH) 2021
DOI: 10.32890/jeth2021.1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Destination Image, Tourist Interest in Travelling and Promotion: The Case of Bedengan, Malang, Indonesia

Abstract: The existence of tourist objects and attractions is the most important component in a tourism activity. Likewise with the existence of tourist attractions in Bedengan, Malang, Indonesia, the number of existing visits has fluctuated. This is because there are several interesting factors encouraging tourists to visit Bedengan such as, its location which is close to several campuses, its large area which makes it suitable to set up a camp, landmass that can be used for outdoor, a very serene view with a narrow ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
1
0
1
Order By: Relevance
“…(Septiandari et al 2021) (Alvianna et al 2020) revealed that the image of the destination plays an important role in understanding the behavior of tourists in traveling. Satisfied travelers tell others good things about the brand, while dissatisfied travelers may throw away or return the product (Hidayatullah, Sutikno, et al 2021).…”
Section: The Role Of Tourist Satisfaction In the Relationship Of Dest...mentioning
confidence: 99%
“…(Septiandari et al 2021) (Alvianna et al 2020) revealed that the image of the destination plays an important role in understanding the behavior of tourists in traveling. Satisfied travelers tell others good things about the brand, while dissatisfied travelers may throw away or return the product (Hidayatullah, Sutikno, et al 2021).…”
Section: The Role Of Tourist Satisfaction In the Relationship Of Dest...mentioning
confidence: 99%
“…Tepatnya, tekanan sosial berasal dari pendapat teman dari mulut ke mulut dan anggota keluarga. Dalam masyarakat kontemporer, dari mulut ke mulut menjadi hal yang vital dalam penyebarannya dan menghubungkan individu dengan informasi tentang degradasi lingkungan dan lebih lanjut menumbuhkan perilaku pro-lingkungan individu (Sweeney et al, 2014) (Zharfaningrum et al, 2020) (Hidayatullah, Sutikno, et al, 2021).…”
Section: Subjective Normunclassified